CONVERSION OF TURBOCHARGED DIESEL ENGINE TO OPERATE SOLELY WITH HYDROUS ETHANOL - Queiroga, B. L. C.; Jaguaribe, E. F.; Gonçalves, M. S. J.; Oliveira, B. L. N.; Rumão, A. S. (Revista de Engenharia Térmica, 2013)
This paper discusses the conversion of a turbocharged diesel engine to operate with hydrous ethanol, using procedures developed in Innovation Lab of UFPB, IL. An diesel engine, brand Perkins, model 1104C-44TAG2, was converted to operate with hydrous ethanol at the time that it amended its compression ratio of 18:1 to 9.3:1, suitable for an Otto Cycle engine to non-occurrence of detonation fuel. Comparing experimental data generated for the converted engine tests (which ranged the ignition advance, stoichiometric air/fuel ratio and rotation at 1800 rpm) with those obtained in tests with the original engine, and converted, 45 kWe, a cost reduction of 34% with Ignition Advance of 20°. It was taken into account in this analysis, and data on fuel consumption, the cost of diesel, R 1.90/liter, and hydrous ethanol, R 0.70/liter. Regarding the gaseous emissions, depending on the load, it was found that the NOX ranged from 50 to 1050 ppm, CO, 1 to 3%, CO2, 12 to 15% and HC 150 to 450 ppm.